Al-Qaedia : In Search of the Terror Network that Threatens the World - Corbin, Jane (New York Thunder's Mouth Press, 2002)
In this new examination of the terror network that threatens the world, an award-winning international journalist shows how Al Qaeda is still a deadly force to be reckoned with.
Include Map and Illustration
Keywords: Bin Laden, Osama, 1957-2011 -- September 11 Terrorist Attacks (2001) -- War on Terrorism (2001-2009) -- Qaida (Organization)